Tác động của các nhân tố bên ngoài doanh nghiệp đến tính thích đáng của chất lượng thông tin kế toán trên báo cáo tài chính - Nguyễn Xuân, Hưng; Phạm Quốc, Thuần (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
Research on information quality is one of the current issues capturing attention of researchers in many fields, such as accounting, information systems, administration, and so on. In an enterprise, accounting information is considered an essential component of management information, playing a role of managing the financial resources for a company and establishing the firm’s competitiveness and success. This study, by using the qualitative method, discovers four external factors affecting the “relevance” of the quality of financial statements information, whereas adopting the quantitative method allows the authors to confirm the impact of several factors, including pressure on tax, listed securities, and independent auditor on the adequacy of quality of financial statements information.